LEGAL IMPACTS OF UNRECORDED MARRIAGE IN SOUTH JAILOLO WEST HALMAHERA IN ISLAMIC LAW AND MARRIAGE LAW NO.1 1974 PERSPECTIVE - Husain, Azmi Djama; Abubakar, Fatum (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
This article analyzes the impact of the law on unregistered marriages on the reality that occurred in Jailolo, West Halmahera. In the last 3 years (2018 - 2020) there were 248 couples who did not register their marriages.This is due to differences in legal regulations governing unrecorded marriage laws. Legal regulations in the Marriage Law and in the Compilation of Islamic Law. This research is a qualitative research. The method used is a field method through observation, interviews and documentation. The approach in this study is through a sociological normative juridical approach.This study found that the impact of marriage law was not recorded in Jailolo Halmahera Barat according to the perspective of Marriage Law No. 1 of 1974 is invalid, the wife can be divorced at any time, the legal status of the children becomes unclear, and the rights of the wife and children to support and inheritance are not guaranteed.Meanwhile, according to the KHI, the legal impact of marriage was not recorded, that as a result of the marriage, they did not get any benefits for the family and even though it was legal in the eyes of religion, it was not legal in the eyes of the state.